Placoid scales in bioluminescent sharks: Scaling their evolution using morphology and elemental composition - Lourtie, Alexia; Duchatelet, Laurent; Straube, Nicolas; Puozzo, Nathan; Grace, Mark A.; Naylor, Gavin J. P.; Delroisse, Jérôme (Frontiers in Marine Science, 2022)
Elasmobranchs are characterised by the presence of placoid scales on their skin. These scales, structurally homologous to gnathostome teeth, are thought to have various ecological functions related to drag reduction, predator defense or abrasion reduction. Some scales, particularly those present in the ventral area, are also thought to be functionally involved in the transmission of bioluminescent light in deep-sea environments. In the deep parts of the oceans, elasmobranchs are mainly represented by the Squaliform order. This study compares ventral placoid scales' morphology and elemental composition of more than thirty deep-sea squaliform species. Scanning Electron Microscopy and Energy Dispersive X-ray spectrometry, associated with morphometric and elemental composition measurements were used to characterise differences among species. A maximum likelihood molecular phylogeny was performed for 43 Squaliformes belonging to all known families of the order. Character mapping was based on the new phylogeny to estimate ancestral character states among the squaliform lineages. Our results highlight a conserved and stereotypical elemental composition of the external layer among all 32 species examined. Phosphorus-calcium proportion ratios (Ca/P) slightly vary from 1.8-1.9, and fluorine is typically found in the placoid scale. By contrast, there is striking variation in shape in ventral placoid scales among the investigated families. Character-mapping reconstructions indicated that the shield-shaped placoid scale morphotype is likely to be ancestral among squaliform taxa. The skin surface occupied by scales appears to be reduced in luminous clades which reflects a relationship between scale coverage and the ability to emit light. In luminous species, the placoid scale morphotypes are restricted to pavement, bristle- and spine-shaped except for the only luminescent Somniosidae, Zameus squamulosus, and the Dalatiidae species Mollisquama mississippiensis. These results, deriving from an unprecedented sampling, show that while there is extensive morphological diversity in placoid scale shape there is little variation in elemental composition among deep-sea elasmobranchs.